Technology to support reminiscence therapy for elderly / Maryani Che Ali - Che Ali, Maryani (2015)
Ageing population has become a global phenomenon. The elderly population are increasing with a high proportion of workers are set to retire. These older workers possess priceless knowledge and they are a very important asset for an organization. However due to the elderly population that mostly characterized by cognitive decline, it caused difficulties in recalling the knowledge and would give an impact of their social lives. Thus this study explored the reminiscence therapy that was introduced to help elderly to recall knowledge and improve their quality of lives. The purpose of this study is to describe the process of reminiscence therapy that has been conducted for elderly and the aim is to propose a suitable technology that can support the process. Qualitative approach has been used in this study because it allows a deeper understanding about the work process on how reminiscence therapy is being conducted. A case study at three case sites has been done and the method used for data collection is observation and interview with the experts. The finding from this study shows that the reminiscence therapy process is contextual, the process dependent on the participant's cognitive level. The reminiscence therapy process is in a continuum from structured to unstructured process. From the findings, among the technology which can support reminiscence therapy process are multimedia technologies, storytelling technology, collaboration technology and centralized database system. The result of the study includes the reminiscence work process and a system support framework. This study contributes towards practice through the development of the work process of reminiscence therapy which can be used by practitioner in the domain of reminiscence therapy. Contribution towards new knowledge is reflected through the work process of reminiscence therapy and system support framework for reminiscence therapy. The system support framework is developed according to the work process obtained through the observation and interview from the real case study.